Evaluation of toxicity studies of Sesbania grandiflora leaves extracts in Wistar albino rats - Sharma, Sharad; Semwal, Bhupesh Chander; Mazumder, Avijit (Journal of Applied Pharmaceutical Research, 2024)
Objective: Sesbania grandiflora is a well-known medicinal plant belonging to the family Fabaceae, and it is used to treat several disorders. The current investigation aims to analyze the negative consequences of short and long-term administration of hydroalcoholic extract of S. grandiflora leaf in experimental animals.  Materials and Methods:  Acute and subacute toxicity were the two phases in which the entire examination was completed. In phase first, acute toxicity was performed at the dose of (2000, mg/kg) and adverse effect was recorded. However, in sub-acute toxicity the effect of different doses of (1000, 2000 and 5000 mg/kg) were studied for twenty-eight days. Animals were euthanized on the last day of the investigation, and selected internal body organs and samples of the blood were taken from each animal for histological, biochemical, and haematological analysis.  Results:  The result of the current investigation showed that the LD50 of S. grandiflora was observed more than 2000 mg/kg, Furthermore, experimental animals did not experience any mortality or alterations in their behavioral patterns when S. grandiflora was administered repeatedly at 1000, 2000, and 5000 mg/kg or in a single dose of 2000 mg/kg.   Besides this, S. grandiflora also did not significantly modify any of the biochemical or haematological markers, or the histological analyses of selected organs. Conclusion: The results of the above research revealed that the orally administration of S. grandiflora extract did not exhibit any apparent harmful effects in experimental animals. Hence, S. grandiflora could be regarded as a safe and can be used for the therapeutic purpose in human being.